2001
DOI: 10.1046/j.1365-2494.2001.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a foliar spray containing phosphorus and zinc on the development, composition and yield of forage maize

Abstract: Forage maize grown in areas where spring temperatures are low and accumulated heat is limited will be restricted in terms of maturity and thus nutritional value. A stagnant growth phase is commonly caused by low temperatures between germination and the five‐leaf stage, which could be caused by reduced mineral availability. The effects on maize plant development and harvest characteristics of supplying phosphorus and zinc to young plants in a foliar spray were investigated. Three different application dates, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
4
13
0
Order By: Relevance
“…Multiple beneficial effects of foliar P fertilizer application in corn (Thavaprakaash, Velayudham, & Panneerselvam, 2006), wheat (Batten, Wardlaw, & Aston, 1986) and barley (Qaseem, Afridi, & Samiullah, 1978) have been documented . Leach & Hameleers (2001), observed a significant increase in both cob index and starch content (b) when P was applied at four-leaf growth stage. Batten, Wardlaw, & Aston (1986) reported that foliar application of KH2PO4 resulted in higher grain yield in winter wheat coupled with the delay in leaf senescence in hot and dry growing conditions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Multiple beneficial effects of foliar P fertilizer application in corn (Thavaprakaash, Velayudham, & Panneerselvam, 2006), wheat (Batten, Wardlaw, & Aston, 1986) and barley (Qaseem, Afridi, & Samiullah, 1978) have been documented . Leach & Hameleers (2001), observed a significant increase in both cob index and starch content (b) when P was applied at four-leaf growth stage. Batten, Wardlaw, & Aston (1986) reported that foliar application of KH2PO4 resulted in higher grain yield in winter wheat coupled with the delay in leaf senescence in hot and dry growing conditions.…”
Section: Discussionmentioning
confidence: 89%
“…The quality as well the yield of crops are enhanced by foliar application of NPK (Römheld & El-Fouly, 1999). The foliar application of P and Zn significantly enhanced the cob index and starch contents http://ijfaas.com of maize but the dry matter production of maize was not effected (Leach & Hameleers, 2001). Phosphorus (P) is the 2 nd major nutrient after nitrogen (N) and it is deficit in soils.…”
Section: Introductionmentioning
confidence: 99%
“…Foliar application of Zn enhances the uptake and accumulation of nitrogen and finally increased the maize grain. Foliar application of Zn significantly improved starch contents of forage maize [32]. In case of greater bioavailability of the grain zinc derived from foliar applications than from soil, agronomic bio-fortification would be a very attractive and useful strategy in solving zinc deficiencyrelated health problems globally and effectively [24,33,34].Therefore, foliar application of nutrients to crop plants is very effective for improving crop growth and yield [35].…”
Section: Introductionmentioning
confidence: 99%
“…Maize was recognized by farmers for a long time as a crop of high response to zinc supply. In temperate regions, due much shorter vegetation and low temperatures prevailing at early stages, maize growth appears to be highly sensitive to many external and internal stresses, which in turn induce grain yield reduction (Leach andHameleers 2001, Subedi andMa 2009). It was recently documented that zinc foliar application is a simple way for making quick correction of plant nutritional status, as reported for wheat (Erenoglu et al 2002) and maize (Grzebisz et al 2008).…”
mentioning
confidence: 96%